Separation of Carbon Dioxide (CO2) from Gas Mixture by Membrane Permeation Process - V. Soesilowati Praptowidodo (Journal of Mathematical and Fundamental Sciences, 2001)
Removal of CO2 from natural gas and combustion exhaust gas have been studied by employing membrane permeation process. In these studies, polysulfone, polyimide and polydimethylsiloxane membranes are used to elucidate the influence of flexibility and rigidity of polymer as well as the influence of polar groups within polymer matrix on gas transport through membrane. The performance of the membranes as specified by its selectivity and permeation flux are measured in terms of the diffusion and sorption coefficients as well as the permeability. It is found that flexibility of the membrane tends to suppress its selectivity while enhancing its permeation flux. On the other hand, rigidity of the membrane together with the polar groups is shown to induce the opposite effects. In both cases however, the selectivity and permeation follow approximately the same qualitative variations with respect to concentration which is suspected to be caused by the plasticization effect in the membrane. It is therefore concluded that a rigid polymer membrane with polar groups is most effective for its performance. Pemisahan karbon dioksida (CO2) dari campuran gas dengan permeasi membranSari. Penghilangan CO2 dari gas alam dan gas buang hasil pembakaran dipelajari dengan cara permeasi membrane. Dalam studi ini membran polisulfon, polimid, dan membran karet silicon (polidimetilsiloksan) dipergunakan dalam rangka mempelajari pengaruh kelenturan dan kekakuan polimer serta pengaruh gugus polar dalam matriks polimer pada perpindahan gas melalui membrane. Kinerja membrane ditentukan oleh seletivitas dan fluks permeasi yang diukur dari besaran koefisien difusi, koefisien sorpsi dan permeabilitas. Hasil percobaan menunjukkan bahwa kelenturan membran cenderung menekan seletivitas namun dapat menaikkan fluks permeasi. Sedangkan kekakuan membrane disertai gugus polat dalam matriks polimer memberikan efek yang berlawanan. Dalam kedua kasus tersebut, seletivitas dan fluks permeasi mengikuti variasi kualitatif yang mirip terhadap pengaruh konsentrasi CO2, diperkirakan dapat menyebabkan efek plastisasi dalam membrane. Disadarkan pada hasil penemuan seperti tersebut di atas, maka dapat disimpulkan bahwa polimer membran kaku dengan gugus polar merupakan membran yang paling efektif untuk penghilangan CO2 dari gas alam dan gas buang hasil pembakaran.